MODEL PEMBELAJARAN KOOPERATIF TIPENUMBERED HEADS TOGETHER UNTUK PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK - Senia Aspadela Jurivi (Jurnal Edukasi dan Penelitian Matematika, 2018)
The aims of this research is to increase understanding of mathematical concepts. In fact, in eight grade MTsN Tanjung Barulak showed that mathematics learning process was still not able to improve students’ understanding of mathematical concepts optimally.It happened because students were’nt really involved in teaching and learning process. One of solutions that couldbe done to increase the students' concepts understandingwasby implementing cooperative learning model of Numbered HeadsTogether (NHT).Type of this research was quasi-experimental with Static Group Design. The samples of this research were class VIII.3 and VIII.2. Instrument of research wasfinal test. Analysis of final test indicates that students’ understanding of mathematical concepts who study by using NHT model is better than using conventional learning.  Keywords – conventional learning, cooperative learning model, numbered heads together,understanding of mathematical concepts.